NASPA 2020 SUBMISSION - Richard Yao:::President::: (2020)
The Division of Student Affairs (DSA) at California State University Channel Islands has developed a comprehensive Student Affairs Data Dashboard that has transformed how DSA data is being employed to evaluate our programs, and perhaps most importantly, has demonstrated the significant role of the DSA in improving student success and closing equity gaps. These efforts have firmly connected the DSA to the academic mission of CSUCI and cultivated more innovative and collaborative partnerships with Academic Affairs, University Advancement and Business and Financial Affairs. This work has facilitated consistent data collection processes for all DSA programs and now provides DSA staff at all levels with immediate access to data to inform evidence-based decision making.